IBD2020 global forum: Results of an international patient survey on quality of care. - Irving, P; Burisch, J; Driscoll, R; Olsson, M; Fullarton, JR; Rodgers-Gray, BS; Travis, SP (Korean Association for the Study of Intestinal Diseases, 2018)
Background/Aims IBD2020 is a global forum for standards of care in inflammatory bowel disease (IBD). The aim of the IBD2020 survey was to identify and describe variations in quality care of IBD. Methods Patients with IBD from Finland, Italy, France, Canada, Germany, UK, Spain and Sweden were surveyed during 2013 to 2014, covering: disease characteristics; impact on life and work; organization and perceived quality of care. Results Seven thousand five hundred and seven patients participated (median age, 39 years [range, 10–103 years]; 2,354 male [31.4%]), including 4,097 (54.6%) with Crohn’s disease (CD) and 3,410 (45.4%) with ulcerative colitis (UC). Median time from symptom onset to diagnosis was 1 year for both CD (range, 0–47 years) and UC (range, 0–46 years), with no clear evidence of improvement in diagnostic delay over the preceding 24 years. Half of the patients (3,429; 50.0%) rated their care as “excellent” or “very good,” with similar results for CD and UC across countries. Five factors were significantly (P<0.01) associated with perceived good quality of care: quality of specialist communication; review consultation being long enough; failure to share information; no access to a dietician; speed of advice. Conclusions The IBD2020 survey has highlighted areas related to quality of care of IBD from the patients’ perspective, with scope for improvement.